Exploring the functional variations of key candidate genes affecting egg production by hypothalamic-pituitary-ovarian axis in chickens - Dandan Wang; Yiqian Zhu; Jiajia Dong; Yihao Zhi; Guanghui Wei; Xiangtao Kang; Xiaojun Liu (Poultry Science)
Potential genetic variants associated with chicken egg production traits have been extensively identified, most of which are located in the non-coding regions of the genome. However, which functional variants really drive the egg-laying phenotype change remain elusive. In the present study, by integrating the previously screened egg-laying related candidate genetic variants, transcriptome data derived from 16 high- and low-yield Gushi chickens, and epigenomic analyses, 22 potential functional variants (PFVs) were systematically identified. These PFVs potentially drive the differences in egg production phenotypes by affecting the expression of 10 egg-laying related key candidate genes in the hypothalamus (ZNF804B, DPP10, NEO1 and GABRG1), pituitary (DPP10 and GNG7), and ovary (PHIP, OSTN, GADD45B, NFXL1 and ADAMTS17). Subsequently, the regulatory activity and function of one PFV, chr3:79510218A>T, located in the third intron of the pleckstrin homology domain interacting protein gene (PHIP), were investigated in chicken ovarian granulosa cells. Association analysis confirmed the significant association of chr3:79510218A>T with egg number from 21 to 43 week of age in Gushi chicken (P = 0.0022) and Guangxi Yao chicken (P = 0.0388), as well as with ovarian PHIP expression levels (P = 0.0010). Functional analysis indicated that the T allele of chr3:79510218A>T enhanced the transcriptional activity and upregulated PHIP expression in vitro by binding transcription factor forkhead box I1 (FOXI1). Furthermore, the knockdown of PHIP led to the inhibition of ovarian granulosa cell proliferation and a reduction in the synthesis and secretion of progesterone (PROG) hormones. Collectively, this study unveil the egg-laying related functional variants and illustrate a potential genetic regulation mechanism, and will help accelerate the molecular design breeding process of chicken egg production.